Social Life During the Anushteginid Dynasty.Social Protection and Population Appeals. (Texas Journal of Philology, Culture and History, 2025)
This article discusses social life during the Anushtegin dynasty, which played an important role in the history of the Uzbek people and statehood. It analyzes the social protection of the population of that time, the appeals of the population, and the policies and role of the rulers of the dynasty in this system, mainly in sources, literature, and historical documents